2010
DOI: 10.1111/j.1365-2672.2010.04913.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron in azoreduction by resting cells of Shewanella decolorationis S12

Abstract: Aim:  To investigate the role of soluble and insoluble iron in azoreduction by resting cells of Shewanella decolorationis S12. Methods and Results:  A series of analytical experiments were carried out. Results showed that insoluble Fe2O3 all delayed the reduction of amaranth but did not inhibit it. Adsorption to Fe2O3 particles by the bacterial cell surface could be the reason leading to the delay in azoreduction. For the soluble iron, an important finding was that azoreduction activities were inhibited by sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The lack of effects of rotenone on Fe(III)EDTA and Fe(II)EDTA‐NO reduction basically agrees with the data in earlier reports . As for NaN 3 , the tolerance of Fe(III)EDTA reduction was also recognized by other research while the effect on Fe(II)EDTA‐NO reduction was inconsistent with Matsubara and Iwasaki's result that NaN 3 decreased the rate of nitrous oxide formation . The doses used and the nature of NO might be contributed to the discrepancies.…”
Section: Resultssupporting
confidence: 87%
“…The lack of effects of rotenone on Fe(III)EDTA and Fe(II)EDTA‐NO reduction basically agrees with the data in earlier reports . As for NaN 3 , the tolerance of Fe(III)EDTA reduction was also recognized by other research while the effect on Fe(II)EDTA‐NO reduction was inconsistent with Matsubara and Iwasaki's result that NaN 3 decreased the rate of nitrous oxide formation . The doses used and the nature of NO might be contributed to the discrepancies.…”
Section: Resultssupporting
confidence: 87%
“…Hence, the results indicated that Fe(III) as an energy source could enrich the biomass, promoting decolorization. On the other hand, the electron transfer cycle in the Fe (III)–dye reaction mixture might be attributed to a redox mediator containing iron and binding protein with lower redox potential than that of azo dyes …”
Section: Resultsmentioning
confidence: 99%
“…Methods to speed up characterisation and collect more data were employed in this study using a simple, high-throughput method employing microplates [38,42]. Resting cells have been utilized in exploring the biological reduction of heavy metals including vanadate [43], selenate [44], chromate [45], reductions and xenobiotics biodegradation such as dyes [46,47], diesel [48], SDS [49], phenol [50], amides [51] and pentachlorophenol [52].…”
Section: Identification Of Mo-reducing Bacteriummentioning
confidence: 99%